(untitled) (Global Journal of Science Frontier Research, 2019)
There are many anecdotal reports on traditional use of camel milk and urine in the treatment of Diabetes Mellitus (DM). The need therefore arises to validate this claim. The objectives of the study is to; compare the effect of camel milk and urine on serum glucose of rats, compare the effect of camel milk and urine on serum lipids of rats and to Compare Different doses of the products on serum glucose and lipids. Thirty-six adult albino rats were used in 4 X 3 factorial experiment involving 4 product treatments and 3 doses. A significant decrease in the blood glucose level in the experimental groups fed camel milk when compared to diabetic untreated (control) group. In treatment group treated with camel urine singly and in combination there was a significant decrease in glucose compared to control. The result shows that there were significant decrease in TG, TC, LDL-C and VLDL-C compared with the control while the HDL was significantly increased. The results indicate that camel milk possess anti-diabetic effects on alloxan induced rats. This study recommended that awareness should be created on the therapeutic value of camel urine and its combination.